Onset and progression of postmortem histological changes in the central nervous system of RccHan™: WIST rats - Weber, Klaus; Domènech, Anna; Kegler, Kristel; Kreutzer, Robert; Mayoral, Francisco José; Okazaki, Yoshimasa; Ortega, Paula; Polledo, Laura; Razinger, Tanja; Richard, Olivia Kristina; Sanchez, Raúl; Warfving, Nils; et al. (Frontiers in Veterinary Science, 2024)
Death initiates a cascade of physiological and biochemical alterations in organs and tissues, resulting in microscopic changes that challenge the histopathological evaluation. Moreover, the brain is particularly susceptible to artifacts owing to its unique composition and its location within the cranial vault. The aim of this study was to compile and illustrate the microscopic changes in the central nervous system (CNS) of rats subjected to delayed postmortem fixation. It also scrutinizes the influence of exsanguination and cooling methods on the initiation and progression of these alterations. Twenty-four Wistar Han outbred rats (RccHan TM :WIST) were sacrificed and stored either at room temperature (18-22 ºC) or under refrigeration (2-4 ºC). Necropsies were conducted at different time points postmortem (i.e., 0.5h, 1h, 4h, 8h, 12h, 24h, 36h, 48h, 7 days and 14 days). Brain sections underwent simultaneous digital evaluation by 14 pathologists until a consensus was reached on terminology, key findings, and intensity levels. Microscopic observations varied among cell types. Glial cells were similarly affected throughout the CNS and showed pericellular halo, chromatin condensation and nuclear shrinkage. Neurons showed two types of postmortem changes as most of them showed progressive shrinkage, cytoplasmic dissolution and karyorrhexis whereas others acquired a darkneuron-like appearance. Neuronal changes showed marked differences among neuroanatomical locations. Additional postmortem changes encompassed: granulation and microcavitation in neuropil and white matter; retraction spaces; detachment of ependyma, choroid plexus, and leptomeninges. Severity of findings after 48 hours at room temperature was higher than after seven days under refrigeration and similar to or slightly lower than after 14 days under refrigeration. No clear differences were observed related to the sex or weight of the animals or their exsanguination status. This work elucidates the onset and progression of autolytic changes in the brains of Wistar Han rats, offering insights to accurately identify and enhance the histopathological evaluation.